2013
DOI: 10.1021/jp311235h
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of OH Radicals with Arizona Test Dust: Uptake and Products

Abstract: Kinetics and products of the interaction of OH radicals with solid films of Arizona Test Dust (ATD) were studied using a low pressure flow reactor (0.5-3 Torr) combined with a modulated molecular beam mass spectrometer for monitoring of the gaseous species involved. The reactive uptake coefficient of OH was measured from the kinetics of OH consumption on Pyrex rods coated with ATD as a function of OH concentration ((0.4-5.2) × 10(12) molecules cm(-3)), relative humidity (RH = 0.03-25.9%), temperature (T = 275-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
(68 reference statements)
2
33
0
Order By: Relevance
“…However, in our opinion, the transformation of H 2 O 2 on the ATD surface is not the main reason for the absence of H 2 O 2 in gaseous products of the HO 2 + ATD reaction. Thus in a recent study from our group H 2 O 2 was distinctly observed as a gaseous product of the interaction of the OH radical with the same ATD surface, although with a relatively low yield of 10 % (Bedjanian et al, 2013). The present results seem to indicate that HO 2 uptake by atmospheric aerosols does not necessarily produce H 2 O 2gas .…”
Section: Discussionsupporting
confidence: 53%
“…However, in our opinion, the transformation of H 2 O 2 on the ATD surface is not the main reason for the absence of H 2 O 2 in gaseous products of the HO 2 + ATD reaction. Thus in a recent study from our group H 2 O 2 was distinctly observed as a gaseous product of the interaction of the OH radical with the same ATD surface, although with a relatively low yield of 10 % (Bedjanian et al, 2013). The present results seem to indicate that HO 2 uptake by atmospheric aerosols does not necessarily produce H 2 O 2gas .…”
Section: Discussionsupporting
confidence: 53%
“…Please note that uptake coefficients reported by Bedjanian et al (2013b) are based on the geometrical area of the rod coated with ATD particles and thus should be considered as the upper limit.…”
Section: Oh Radicalsmentioning
confidence: 99%
“…5, with the most evident one being the effect of RH. Park et al (2008) found that γ (OH) increased significantly with RH for both SiO 2 and Al 2 O 3 , while Bedjanian et al (2013b) suggested that γ (OH) showed a negative dependence on RH. It is not clear yet whether different minerals used by these two studies can fully account for the different RH dependence observed.…”
Section: Oh Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black contour lines show ClO x mixing ratios from the Mt Pinatubo simulation (S2) in ppbv. (Romanias et al, 2012) and OH radicals (Bedjanian et al, 2013) -and found that the measured uptake coefficients varied only by a factor of 2-3 or less across a wide temperature range. However, it is unclear whether temperature would have a significant effect on γ (ClONO 2 ) for TiO 2 particles, and therefore our simulated impact of heterogeneous reaction of ClONO 2 with TiO 2 on stratospheric chemistry may have large uncertainties.…”
Section: Implication For Stratospheric Particle Injectionmentioning
confidence: 97%